2019
DOI: 10.1093/jee/toz207
|View full text |Cite
|
Sign up to set email alerts
|

Beauveria bassiana (Ascomycota: Hypocreales)–treated Diamondback Moth (Lepidoptera: Plutellidae) Larvae Mediate the Preference and Functional Response of Euborellia annulipes (Dermaptera: Anisolabididae) Nymphs

Abstract: Biological control is one of the strategies to reduce populations of diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), the major pest of brassica. Entomopathogen-based biopesticides are recommended and used for its control, reducing the constant use of chemical pesticides. Predators and/or fungal entomopathogens have an increasing interest to be used against diamondback moth, and the compatibility of these control agents in the field is important for pest management. Here we experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The type II response has been reported for E. annulipes that prey on lepidopteran pests. However, some authors have found that the functional response can change to type III depending on the temperature or whether the prey is infected by entomopathogenic fungi (Nunes, Dantas, et al, 2019; Nunes, Ramalho, et al, 2019; Nunes, Truzi, et al, 2019). Attack rate ( a ) and handling time ( h ), which determine the slope and height of a functional response curve, respectively (Holling, 1959), did not differ significantly between earwig males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The type II response has been reported for E. annulipes that prey on lepidopteran pests. However, some authors have found that the functional response can change to type III depending on the temperature or whether the prey is infected by entomopathogenic fungi (Nunes, Dantas, et al, 2019; Nunes, Ramalho, et al, 2019; Nunes, Truzi, et al, 2019). Attack rate ( a ) and handling time ( h ), which determine the slope and height of a functional response curve, respectively (Holling, 1959), did not differ significantly between earwig males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has also shown that some synthetic chemical insecticides, such as spinosad, acetamiprid, and chlorpyrifos-ethyl, have no effects on the predation activity of earwigs [38], when the insects are exposed to a dose or concentration that isn't lethal [39]. On the other hand, infection by pathogens is a factor that affects predation in some insects [40] [41], however, according to [42],…”
Section: Food Preferencementioning
confidence: 99%